Binding of divalent and higher valent metal ions to surfactants and polyelectrolytes. (November 2017) - Stewart, Beverly; Kogej, Ksenija; Luísa Ramos, M.; Valente, Artur J.M.; Burrows, Hugh D.
Abstract: Interactions between ionic organic systems, such as surfactants or polyelectrolytes, and divalent or higher valent metal ions have been studied extensively for many years, but still present challenges in understanding the type and nature of interactions involved and also the driving forces behind metal ion binding. Graphical abstract: Highlights: Present recent highlights in metal binding in surfactant and polymer systems Thermodynamic and kinetic considerations Hierarchical assembly of microtubes as biosensors A general route to chiral nanostructures from helical polymers Deprotection strategy of a BODIPY visible light photocatalyst